Mudzakkar dan Muannats: Sumber Pendidikan Islam Bias Gender - Setiyawan, Agung (Jurnal Pendidikan Islam, 2014)
Grouping Arabic nouns into kinds of mudzakkar and muannats often become the source of gender biases understanding. Such classification is one of the characteristics of the Arabic language which is different from any other languages. With the existence of the classification, it is understood that the Arabic language provide strict distinction between sex differences. Gender bias in the Arabic language is very interesting to be examined not to denigrate the language, but to understand what exactly is a gender bias in the Arabic language so that we do not get trapped in the wrong understanding and seem condescending. This study concluded that when we examined more deeply, the mudzakar and muannats characteristics that exist in Arabic language give uniqueness and richness meaning that may not be found in other languages.